1989
DOI: 10.1017/s002193200001806x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of breast-feeding and post-partum amenorrhoea in Orissa

Abstract: A life table analysis is made of the duration of breast-feeding and post-partum amenorrhoea in Orissa, India, taking one variable at a time using data from a baseline survey of fertility and mortality (BSFM) conducted on the lines of the World Fertility Survey. Then a multivariate (proportional hazard) analysis showed that socioeconomic factors including residence, caste status and education influence the breast-feeding and postpartum amenorrhoea periods. There was no effect of maternal age on the length of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 7 publications
3
18
0
Order By: Relevance
“…Other studies have shown that multiparae menstruate a little later than primiparae (Liestol et al, 1988;Adnan & Bakr, 1983) and the postpartum amenorrhoeic period increases with increasing age (Khan & Siraj, 1986;Srinivasan et al, 1989). This was confirmed in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Other studies have shown that multiparae menstruate a little later than primiparae (Liestol et al, 1988;Adnan & Bakr, 1983) and the postpartum amenorrhoeic period increases with increasing age (Khan & Siraj, 1986;Srinivasan et al, 1989). This was confirmed in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…In general, birth intervals (of second and higher orders) are comprised of long durations of post-partum amenorrhoea associated with nearly universal patterns of prolonged breast-feeding (Bhattacharya, Pandey & Singh, 1988;Singh, 1990). The duration of post-partum amenorrhoea in India varies between 10 and 14 months (Potter, 1963;Singh, 1990;Singh & Bhaduri 1971;Srinivasan, Pathak & Pandey, 1989). Furthermore, death of the infant leads to a short duration of post-partum amenorrhoea.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] This study indicates that around 65% of women had never used any contraception. Majority of women were breastfeeding their children for shorter duration of less than 5 months.…”
Section: Discussionmentioning
confidence: 99%